Analysis of the B2 first reading and use of English section about accessibility, cultural bias, and feedback - Haidir Algi Gaffar Faridha; Meylisa Hadi Yanti; Rafi Pramana Putra (English Learning Innovation, 2025)
The B2 First, formerly known as the First Certificate in English (FCE), is an English test for non-native speakers to study and/or work in an English-speaking environment. The Reading and Use of English (RUE) section has high cognitive demands and is commonly used in academic and professional settings. The analysis evaluates the Cognitive Framework and Messick’s theory of validity (Messick, 1995). The limited accessibility for Specific Learning Differences (SpLDs) candidates, the culturally biased content, and the lack of explanation in the feedback are the key areas. The study examines task format, linguistic demands, and cognitive load to understand how these factors may impact different groups of test takers. By identifying these challenges, the research aims to support the development of more inclusive and equitable practices in advanced English language assessment. This study applied Messick’s theory of validity (1995) and Weir’s Socio-Cognitive Framework to a qualitative analysis of the 2022 RUE sample paper and official preparation resources. Findings indicate that limited accommodations exist for SpLD candidates, such as minimal adjustments in computer-based formats, but these remain insufficient. The content often reflects Western cultural contexts, potentially disadvantaging learners from different backgrounds. In addition, the lack of explanatory feedback in official materials restricts the test’s learning value and reduces positive washback, particularly for SpLD learners who benefit from explicit guidance. The study concludes that while the B2 First remains a valuable global certification, it requires more inclusive accommodations, culturally varied texts, and integrated feedback systems to ensure fairness and validity.